Review of virtual reality and motion capture in martial arts training - Mohd Jelani, N. A.; Zulkifli, A. N.; Ismail, S.; Yusoff, M. F. (International Journal of Interactive Digital Media, 2019)
Advances in computer technology of today`s three-dimensional graphics coupled with the emergence of a variety of powerful devices have provided many benefits to training applications utilizing Virtual Reality and Motion Capture technologies. The use of these technologies offers a unique experience to the user by offering superior immersive representation as well as realistic motion training system. This paper discusses on Virtual Reality and Motion Capture technologies. It also reviews some of the related studies pertaining to the used of Virtual Reality and Motion Capture technologies in martial arts training. Based on this review, it can be concluded that the use of Virtual Reality and Motion Capture technologies in martial arts training offers many benefits and advantages. Therefore, the combination of these technologies has been proposed as the best approach for self-directed martial arts training.